Adaptation of Migrating Betawi People: Existences, Forms, and Developments: Adaptation of Migrating Betawi People: Existences, Forms, and Developments - Deska Fitriyani; Yoyok Hendarso; Yunindyawati Yunindyawati (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
Adaptation of migrating Betawi people as the ethnic migrant in urban areas is an interesting social phenomena related to urbanism. This study aims to analyze the urbanism or the way of life of the Betawi people in Palembang city. This study used the social definition paradigm, an ethnography research method. The data were the Ethnic Betawi group in the Kebon Sirih and the Lorong Jambu areas.The data were obtained from the primary data and the secondary data. The primary data was obtained through participatory field observations, and in-depth interviews, meanwhile the secondary data was obtained from articles or journals. In analyzing the data, codes system and coding were used. Field observations were carried out in Kampung Betawi, Kebon Sirih and Talang Betawi Villages, Lorong Jambu. Interviews were conducted to participants, the Betawi people, used purposive sampling or based on certain characteristics. The results of the study indicated that the urbanism or a way of life of the people in Palembang was to adjust to the environment in terms of work to meet their daily needs. In addition, it adopted the Palembang wedding tradition when the Betawi people are married. The results showed that the people acculturate with the Palembang culture, specifically in wedding tradition.